Spatiotemporal distributions of halocarbons in the marine boundary air and surface seawater of the Changjiang estuary and its adjacent East China Sea. (March 2019) - Yuan, Da; He, Zhen; Yang, Gui-Peng
Abstract: Spatiotemporal distributions of volatile halogenated organic compounds (VHOCs) were investigated in the marine boundary air and surface seawater of the Changjiang (Yangtze River) estuary and its adjacent East China Sea in two cruises from March 11, 2015 to March 21, 2015 and from July 9, 2015 to July 20, 2015. Results revealed that the concentrations of released chlorofluorocarbons (CFCs) such as CFC-12, CFC-11, and CFC-114 in China decreased, suggesting that limitations set by the Chinese government on CFCs production and consumption have taken effect. Atmospheric concentrations of CFCs were affected by local industrial sources of emission and transport of terrestrial pollutants from coastal areas to varying degrees. Seasonal variations in atmospheric VHOCs were probably due to seasonal differences in prevalent monsoon and biogenic production. In the study periods, the investigated area was an essential source of atmospheric CH3 Br and CH3 I but was a net sink of CFC-12, CFC-11, and CH3 Cl. Highlights: Distributions and sources of VHOC over this estuary were studied for the first time. VHOC mixing ratios exhibited significant spatiotemporal variations in the study area. Coastal emissions contributed to the high atmospheric VHOC mixing ratios. Elevated levels of VHOC in the Changjiang estuary were related to terrestrial input. Changjiang estuary was a net source of atmospheric CH3 Br and CH3 I.